Modeling Textured Translucent Materials with Lazy Solid Texture Synthesis - Dong, Yue; Lin, Steve; Guo, Baining (Material Appearance Modeling: A Data-Coherent Approach, 2013)
An algorithm is introduced for rapidly synthesizing solid textures from a set of 2D example images. In contrast to previous techniques, this method restricts synthesis to a subset of the voxels, while enforcing spatial determinism. A major difficulty lies in reducing the dependency chain of neighborhood matching, so that each voxel only depends on a small number of other voxels. The key idea is to synthesize a volume from a set of 3D candidates, each being a triple of interleaved 2D neighborhoods. An efficient algorithm is presented to carefully select in a pre-process only those candidates forming consistent triples. This significantly reduces the search space during subsequent synthesis. The result is a new parallel, spatially deterministic solid texture synthesis algorithm which generates high resolution solid textures on surfaces within seconds. With a GPU implementation, this method can interactively synthesize new textures for surfaces that appear when breaking or cutting objects.